Factors Influencing the Service Quality for Customer Satisfaction on Parcel Service Safety in the Postal and Courier Industry: Analysis Using Structural Equation Modelling. - Aziz, Zuraimi Abdul; Nik Hussin, Nik Syuhailah; Mukhtar, Dzulkifli; Nordin, Nurnaddia; Nordin, Nurhaiza (Pertanika Journal of Social Sciences & Humanities, 2025)
In the courier sector, the effectiveness and dependability of the last-mile delivery phase are crucial factors in determining the total quality of service provided to customers. Courier services are also expected to provide valuable service quality to their customers. Even though the growth trend is encouraging, many courier companies find it difficult to capitalise on the rising demand for their services because of intense competition and industry pressure to reduce service rates. As customer expectations continue to rise, companies are exploring innovative solutions to improve last-mile delivery. Therefore, the study aims to determine how specific dimensions of service quality affect customer satisfaction in the courier industry. A convenient sampling approach was employed to gather data from 245 respondents who completed a survey questionnaire for this study. Further, hypotheses were tested through a quantitative method using partial least square structural equation modelling (PLS-SEM). This research revealed an insignificant effect of reliability, responsiveness and tangibility on customer satisfaction. In contrast, empathy and assurance were found to have a significant and positive effect on customer satisfaction. These findings establish a foundation for more in-depth research on how last-mile delivery contributes to customer satisfaction.